Confronting Aristotle's Ethics : ancient and modern morality - Garver, Eugene (University of Chicago Press, 2006)
What is the good life? Posing this question today would likely elicit very different answers. Some might say that the good life means doing good?improving one?s community and the lives of others. Others might respond that it means doing well?cultivating one?s own abilities in a meaningful way. But for Aristotle these two distinct ideas?doing good and doing well?were one and the same and could be realized in a single life. In Confronting Aristotle?s Ethics, Eugene Garver examines how we can draw this conclusion from Aristotle's works, while also studying how this conception of the good life rel.